Effects of precursor concentration on morphologies of Cu2O micro/nanocrystals and properties of CO self-sustained catalytic combustion. (1st April 2021) - Ma, Pandong; Teng, Zihao; Hao, Qinglan; Kang, Running; Li, Bei; Bin, Feng; Dou, Baojuan
Graphical abstract: The reaction pathways of CO oxidation over the (1 0 0), (1 1 0) and (1 1 1) crystal planes of Cu2 O. Highlights: Morphologies of Cu2 O micro/nanocrystals were controlled by simply changing precursor concentration. Increase of precursor concentration results in more exposure of active crystal plane of Cu2 O. Activity of CO self-sustained catalytic combustion on Cu2 O increases with precursor concentration. Coordination unsaturated Cu and O on the (1 1 1) and (1 1 0) planes promote CO oxidation. Abstract: The self-sustained catalytic combustion is one of the most effective ways to remove high concentration CO at low temperature. In this paper, Cu2 O micro/nanocrystals with different morphologies were successfully synthesized by changing the precursor concentration using liquid phase reduction method. The obtained Cu2 O were characterized using SEM, XRD, XPS, H2 -TPR and O2 -TPD, and the relationship between the catalytic performance and morphology was analyzed based on CO-TPD-MS and activity evaluation results. It was found that high precursor concentration leads to more exposure of active crystal planes of Cu2 O. Compared with Cu2 O-1 exposing only (1 0 0) crystal planes, Cu2 O-5, the precursor concentration of which is 5 times of Cu2 O-1, exposes (1 0 0) and (1 1 0) crystal planes. Cu2 O-9, with 9 times of precursor concentration of Cu2 O-1, exposes (1 0 0), (1 1 0) and (1 1 1) crystal planes simultaneously. All the obtained Cu2 O with different precursor concentrations can achieve self-sustained CO catalytic combustion, and the catalytic activity increases with increasing precursor concentration (Cu2 O-1 < Cu2 O-5 < Cu2 O-9). The results prove that unsaturated coordination of Cu and O on the (1 1 1) and (1 1 0) planes can enhance the corresponding reducibility, adsorption and activation of gaseous oxygen, consequently promoting the CO oxidation to CO2 over Cu2 O-9.